Pedagogical Creativity as a Factor of the Professional Development of the Teacher-Teacher - Dildora Nadzhatbekovna Kadirova; Solieva Mastura (Research Parks Publishing LLC, 2021)
The article examines the issues of the formation of individuality in a teacher, contributing to the upbringing of a child's creative personality. The more diverse personalities there are among teachers, the more likely they are to teach children who have many different and at the same time useful individual qualities.